Symbolic Power and the Discursive Construction of Obedience: Media Representations of Kiai–Santri Relations in the Context of Bida’ah Series - Ravik Karsidi; Faline Izza Nisa'u (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
This study examines the dynamics of power and obedience in the kiai-santri relationship as represented in the Malaysian series Bida'ah, by emphasizing the pesantren institution as a space for the production of symbolic power. The focus of this study is in the realm of sociology of power, media, and religious culture. This research is important because media representations play a role in shaping public perceptions of traditional authority structures in Malay Islam. The research method used is qualitative-ethnographic with a sociological-cultural approach, through narrative observation of the Bida’ah series and in-depth interviews with seven alumni of pesantren salaf in Jember, East Java. The results show that the kiai figure is represented as a symbolic power center with inviolable spiritual-charismatic authority, while santri show structural and emotional obedience within a patron-client framework. Non-verbal communication symbols and a culture of “pekewuh” reinforce this structure of domination. The findings also show symbolic resistance and reinterpretation of values by santri as a form of negotiation against the kiai's authority. This research contributes to broadening the understanding of power relations in traditional Islamic education and how popular media reproduce or criticize these structures. The findings suggest the importance of revisiting the dominant narrative in pesantren culture to be more inclusive of social change and critical thinking.